Sosialisasi Peran Pancasila Dalam Kehidupan Sehari-Hari Pada Murid SDN Harapan 212 - Fathimah Ghaida Nafisa; Reighina Faridah Solihah; Risa Risa; Maulia Depriya Kembara (International Forum of Researchers and Lecturers, 2024)
The principles of Pancasila play an important role in shaping children's character from an early age, but a lack of understanding of them can have negative impacts, such as the increase in bullying cases and the decline in children's interest in national anthems. This research aims to inform readers about the rise of bullying cases among children as well as the harmful effects of their lack of interest in national anthems, which in turn can raise awareness of the importance of the early introduction and application of Pancasila principles. The research method used is descriptive analysis to describe the meaning of Pancasila as the basis of the state, the importance of the application of Pancasila characters for elementary school children, the meaning of bullying, the factors that cause bullying, and the cause of the large number of children who do not memorize national anthems. Based on the results of the study, a lack of understanding of Pancasila principles can cause children to lose sight of the importance of respecting differences and understanding the values of equality. The implication can lead to bullying behavior among children as well as declining their interest in national anthems. This leads to the need to increase public awareness of the important role of Pancasila in shaping children's character, preventing bullying behavior, and declining interest in national anthems.